A feedback interpretation of the Doyle-Fuller-Newman lithium-ion battery model - Drummond, R; Bizeray, A; Howey, D; Duncan, S (Institute of Electrical and Electronics Engineers, 2019)
The Doyle–Fuller–Newman “psuedo-2-D” electrochemical model of a lithium-ion battery is shown to have a feedback structure when electric double-layer effects are included. This opens the possibility for the model to be rigorously analyzed using input–output systems theory. Several immediate consequences of the feedback structure are discussed, including observability and well-posedness issues, and an application to reduced-order modeling is described.